2020
DOI: 10.1111/ijpo.12747
|View full text |Cite
|
Sign up to set email alerts
|

Implicit and explicit fat bias among adolescents from two US populations varying by obesity prevalence

Abstract: Summary Background Research shows that explicit (reported) and implicit (unconscious) bias are distinct constructs varying by socioecological context. Implicit bias better predicts poor health outcomes related to chronic psychosocial stress. Objectives Variation in fat bias was identified in two populations of adolescents in Indiana counties with relatively high (Lawrence) and low (Monroe) obesity prevalence. Methods Adolescents (n = 185) aged 14‐18 years were recruited October 2017‐2018. Explicit fat bias was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 51 publications
0
8
1
Order By: Relevance
“…As these results suggest, perceived body weight norms were associated with normative perceptions of healthy bodies; however, the direction of this relationship was surprising given recent findings that implicit anti‐fat bias among Indiana adolescents was significantly lower in populations with higher obesity prevalence (Cullin, 2020). Thus, one might expect that as perceived average body weight increases, larger bodies would be less likely to be perceived as abnormal (i.e., unhealthy), but this was not the case.…”
Section: Discussionmentioning
confidence: 58%
“…As these results suggest, perceived body weight norms were associated with normative perceptions of healthy bodies; however, the direction of this relationship was surprising given recent findings that implicit anti‐fat bias among Indiana adolescents was significantly lower in populations with higher obesity prevalence (Cullin, 2020). Thus, one might expect that as perceived average body weight increases, larger bodies would be less likely to be perceived as abnormal (i.e., unhealthy), but this was not the case.…”
Section: Discussionmentioning
confidence: 58%
“…Results from testing P 1 indicated that perceived fat stigma and degree of exposure to obesity during adolescence were not statistically related, thus, statistical norms around body fat did not predict normative views in regards to these variables for this sample. It is possible there is no relationship between obesity prevalence and fat stigma, but this does not seem likely given that implicit anti‐fat bias has been shown to vary by obesity prevalence among adolescents in Indiana (Cullin, 2021) and higher exposure to obesity has been show to increase acceptance of higher proportions of body fat (Robinson & Christiansen, 2014). One possible reason no association was found in this sample is the limited range of variation in obesity levels (24%–34%) between counties.…”
Section: Discussionmentioning
confidence: 99%
“…Anthropological work has previously demonstrated that normative ideas about body fat around the globe vary depending on changes in obesity prevalence (Brewis et al, 2011) as well as ecological context (Brewis & Wutich, 2012). Furthermore, the threshold for acceptable weight status is thought to be sensitive to the distribution of modal body types within a population (Robinson, 2017), and, in the US state of Indiana where the present study took place, unconscious anti‐fat bias was recently found to be higher among adolescents living where obesity prevalence is relatively low (Cullin, 2021), which is important given that such implicit bias is thought to be a strong driver of discrimination and prejudice (Brewis & Wutich, 2012). These findings suggest that variation in body sizes people observe around them may inform normative ideas and beliefs about weight or body size, which could subsequently drive stigmatizing thoughts and behaviors as well as discriminatory policy and treatment.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…To date, childhood obesity has reached epidemic levels and represents a major public health concern 1 . Besides experiencing short‐and long‐term physical health problems, youth with obesity are at increased risk for many different psychosocial stressors (e.g., weight stigma, parent–child attachment difficulties, …) 2–6 on top of the normative challenges they face. These age‐related vulnerabilities include emotional instability, an increase in risk‐taking behaviour, family difficulties and academic pressure 7,8 .…”
Section: Introductionmentioning
confidence: 99%